Enhancement of Structural, Electrochemical, and Thermal Properties of Ni‐Rich LiNi0.85Co0.1Mn0.05O2 Cathode Materials for Li‐Ion Batteries by Al and Ti Doping. Issue 1 (15th October 2020) - Levartovsky, Yehonatan; Wu, Xiaohan; Erk, Christoph; Maiti, Sandipan; Grinblat, Judith; Talianker, Michael; Aurbach, Doron
Abstract: Ni‐rich layered oxides LiNi1‐ x ‐ y Co x Mn y O2 (1− x − y >0.5) are promising cathode materials for the new generation of Li‐ion batteries suitable for electro‐mobility due to their high energy density, good rate capability, and relatively low cost. However, their main drawback is poor cycling performance, particularly at elevated temperatures. In this research, it is demonstrated how doping with Al and Ti, using straightforward solid‐state mixing synthesis, can dramatically enhance the structural, electrochemical, and thermal properties of LiNi0.85 Co0.1 Mn0.05 O2 (NCM85). The capacity retention of Al‐doped and Ti‐doped cathodes after 100 cycles at 100 % DOD at 1 C and 45 °C using standard electrolyte solutions could reach nearly 99 % and 78 %, respectively, while the capacity retention of the undoped material was less than 74 % in similar experiments. Doping with Al and Ti facilitates the Li intercalation processes and reduces voltage hysteresis. Structural study of the cycled cathodes shows that doping with Al, and to a smaller extent with Ti, reduces the formation of cracks in the particles of the cathode materials upon cycling, consequently reducing degradation. Thermal studies show that doping with Al or Ti improves the thermal stability of these cathode materials. Highly interesting is the correlation between the morphology and thermal stability, impedance properties and the electrochemical characteristics as a function of doping. Abstract : To be rich and doped : The influence of Al and Ti doping on the structural, electrochemical and thermal properties of NCM85 cathode materials is studied. Both Al‐ and Ti‐doped cathode materials show superior electrochemical, structural and thermal properties compared to the reference. The coherence between the different properties is discussed and demonstrated.